Penerapan Manajemen Risiko : Studi Kasus pada UMKM Es Teh Djoeragan Jember - Ainul Diniah; Rosma Hani Febrianti; Silatur Rumsiyah; Nurul Qomariah; Nursaid Nursaid (BUDGETING : Journal of Business, Management and Accounting, 2023)
Risk management is important for MSMEs because risk management is useful for gathering information about possible risks that will occur, as well as for developing strategies that need to be implemented for Djoeragan Ice Tea MSMEs. This research aims to find out the application of risk management and describe or describe the activities at the Djoeragan Jember Es Teh MSME. This research uses a qualitative descriptive approach using risk analysis in management. The results of the analysis show that the implementation of risk management at Es Djoeragan Jember MSMEs has been implemented well for financial risks, marketing risks, while for HRM risks it is still not good. It is proven that there are still errors in the calculations carried out by HR at Djoeragan Ice Tea MSMEs. Therefore, it is important for Djoeragan Ice Tea MSMEs to improve and implement good risk management so that they can minimize risks that occur in the future. Keywords: Business, Financial risk, MSMEs, Risk management.